Antibody responses after two doses of SARS-CoV-2 mRNA-1273 vaccine in an individual with history of COVID-19 re-infection. (June 2022) - Inada, Makoto; Ishikane, Masahiro; Terada, Mari; Matsunaga, Akihiro; Maeda, Kenji; Iwamoto, Noriko; Ujiie, Mugen; Kutsuna, Satoshi; Morioka, Shinichiro; Ishizaka, Yukihito; Mitsuya, Hiroaki; Ohmagari, Norio
Highlights: A patient who suffered from COVID-19 re-infection and received 2 doses of vaccine. Antibody against spike protein and neutralizing activity decreased in 1 year. Antibody titers increased after both the first and second vaccine doses. A single booster after COVID-19 re-infection may be sufficient for protection. Abstract: We present a case of a 58-year-old Japanese man with a history of 2 previous COVID-19 infections, who received 2 doses of mRNA-1273 vaccine. We are not aware of any previous study regarding antibody tendency after 2 infections and 2 vaccinations. We evaluated his IgG titer of antispike protein and neutralizing activity from the first infection before and after 2 doses of vaccine. Both antispike IgG titer and neutralizing activity showed a tendency to decline almost 1 year after initial infection; they rapidly increased after the first vaccination, and they remained high after the second vaccination. Although this is a single case report, it seems to have generalizability because the findings are consistent with previous reports regarding single infections or 3 doses of vaccination. Our findings suggest that a single booster shot may provide sufficient protection and aid the understanding of immunologic responses of vaccination in patients with COVID-19 with history of re-infection.